A non-contact human-computer interaction application design based on electrostatic current of human body. (2016) - Han, Qingwei; Chen, Xi; Tang, Kai; Li, Pengfei
This paper puts forward a non-contact Human-Computer Interaction (HCI) method applied to game control based on electrostatic current of human body. By setting an electrode array, the induced current signals generated on the electrodes caused by hand motions can be measured by detection circuit and collected into PC by NI series M high-speed data acquisition device PXI6259. The direction of a hand motion can be figured out by processing the signals with LabVIEW programming. Furthermore, a game (Mary) programmed by LabVIEW can be played with this non-contact HCI technique, the corresponding hand motions: up, down, left and right can control the jump, squat, backward and forward motions of the game object Mary. After repeated experiments, the feasibility of this method has been proved. Namely, a non-contact controlling of a game can be realised with the HCI method based on electrostatic current of human body.